Innovative Study of Indian Marketing And Advertising Sector: A Creative Approach - Giri, Ashok V. (Archives of Business Research, 2017)
In today’s media landscape where it’s very difficult to shape consumers attitude and intentions and move them to next level of buying process, advertisers find it even more difficult and challenging to break through the clutter of competing advertisement. The advertising industry has experienced dynamic changes over the last several decades. The importance of creativity factor in advertising has got wide recognition by many researchers, practitioner, but there is a miss of true & systematic research to define advertising creativity and how it relates to ad effectiveness. The review study discusses some campaigns that have left their strong impression on consumers. The presented review study tries to come up with some evidence of creativity by reviewing expert views, past literature in advertising, studied advertising campaign and marketing activities. The study discusses different forum on how creativity works, and what makes an ad to travel good or poorly. It summarized the value of creativity in advertising through Expert interviews, published material and related secondary data to understand the logic. The changes have been good in terms of Technology advancement, Medium and more methods to attract consumers and on Creativity. This paper represents how creativity impacted advertising, also understanding the value of creativity in advertising through the review of various literatures.